Penerapan Metode Monte Carlo Untuk Mendukung Estimasi Stok Produksi Kue Kering - Rani Purbaningtyas (Benchmark, 2023)
Producing and selling pastries is one of the efforts that can be done to generate additional income, it is also possible to become a main source of income. The problem faced by Narendra pastry producers is that they want to ensure the availability of stock of the cookies they produce so that consumers and resellers are not disappointed if the desired product variant is not available in stock. The Monte Carlo method is the method chosen to predict sales data for Narendra's pastries based on historical sales data for the previous period. The outcome of this Monte Carlo prediction will later become a reference for how much stock of pastries should be produced for each variant. The results showed that the output of the Monte Carlo method had an accuracy rate of 93% for the nastar cookie product variant. With an accuracy rate of 93%, the Monte Carlo method can be used to predict the stock of other pastries variants in the next period.